2013
DOI: 10.3126/saarctb.v10i1.8674
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and CD4 Cell Count Pattern of TB Co-infection Among HIV Infected Individuals In Nepal

Abstract: Background: Mycobacterium tuberculosis (TB) and Human Immunodefi ciency Virus (HIV) infections are two major public health problems in many parts of the world, particularly in developing counties like Nepal. The objective of the study is to fi nd out prevalence and clinical presentation of the TB co-infection among HIV infected individuals and pattern of CD4 cell count in relation to types of TB and response of ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…At initial presentation, the mean CD4 count was 174.47 cells/μl -following 6 months of treatment, which increased to 300.49 cells/μl. Other studies by Niraula et al (2013) [7] and Prabakaran et al (2013) [18] also had the similar findings.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…At initial presentation, the mean CD4 count was 174.47 cells/μl -following 6 months of treatment, which increased to 300.49 cells/μl. Other studies by Niraula et al (2013) [7] and Prabakaran et al (2013) [18] also had the similar findings.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, mean age of the patients was 39.4 ± 8.42 years. Other studies by Kamath et al (2013) [6] , Niraula et al (2013) [7] , Ogbuinya et al (2014) [8] , Mudda et al (2014) [9] , Xavier et al (2013) [10] , Singh et al (2013) [11] also had the similar findings.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…4 As HIV progresses there is cutaneous energy, as well as impaired tissue containment of Mycobacteria leading to widespread dissemination of the organism. 5 CD4 counts are critical in the control of infection with Mycobacterium tuberculosis, as quantitative and qualitative deficiency of these effector cells in HIV 6 Unlike other opportunistic infections which have a selective range of CD4 counts in which the disease occurs, TB occurs throughout the course of HIV. The interaction between HIV and TB in persons with coinfection is bi-directional and synergistic.…”
Section: Concomitant Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…Similar results are reported by others studies. 4,13,14 Magnitude of CD4 cell recovery may depend on variety of factors, including maintenance of virologic suppression with ART, age and CD4 count at ART initiation 6 . In this study, minimal recovery of CD4 counts was observed in patients who were >50 years of age.…”
mentioning
confidence: 99%